Public administration in Southeast Asia : Thailand, Philippines, Malaysia, Hong Kong and Macao - Berman, Evan M. (Public administration and public policy, 2011)
Focuses on developments in public administration in countries which are among the fastest growing economies in the world. This book explores their practices and approaches